Dinamika Kebijakan Pendidikan Islam dan Implementasinya di Madrasah - Salsabila Fitria Salsa; Hapni Hasibuan; Mutiah Nasution; Rahmat Siregar (Universitas Islam Nusantara Al-Azhaar Lubuklinggau, 2025)
This research is motivated by the problem in the implementation of Islamic education policies in madrassas which continue to change with the times but is still based on the values of the Qur'an and Hadith. The purpose of this research is to describe, analyze, and explain how Islamic education policies are applied in the process of religious learning and habituation in madrasah. This research uses a qualitative approach with a case study design, involving one main informant, namely the Deputy Head of Madrasah in the field of curriculum who has more than a decade of experience in managing education policies. Data was collected through in-depth interviews, and observations. The results of the study show that policy implementation is carried out through the integration of general and religious lessons, strengthening manners and morals, as well as worship habits such as reading the Qur'an, congregational prayers, and religious mentoring. Teachers play a central role as educators as well as character builders. The challenges that arise include administrative constraints, time constraints, and variations in teachers' digital skills. This study concludes that the implementation of Islamic education policies has a positive impact on students' motivation to learn and the formation of religious attitudes and has important implications for improving policy management in madrasah.